The Renaissance of Shi'i Islam Facets of Thought and Practice - Daftary, Farhad; Esots, Janis (Shi'i Heritage Series, 2022)
Examines the flourishing of Shi'i Islam during the 15th - 17th centuries with a focus on its diverse groups, movements and strands of thought that have not yet been explored